Greening the office: Saving resources, saving money, and educating our patients - Stacy Blum, DO; Molly Buckland, DO; Todd L. Sack, MD, FACP; David Fivenson, MD, FAAD (Wolters Kluwer, 2021)
Objective: Dermatologists can benefit from adopting environmental sustainability in the management of their practices. We can also use opportunities to share best practices in environmental stewardship concepts with our colleagues, patients, and communities. Herein, we review easy steps for any health care professional, and dermatologists in particular, to adopt environmental sustainability and become more active in the fight against climate change. Methods: This study included a select literature review, an identification of resources, and an overview of MyGreenDoctor.org. Results: Many simple, cost effective, energy saving resources were identified. A reference list of climate change resources for health are organizations to help with lower their carbon footprints, educating their staff and patients, and advocacy for better environmental stewardship is presented. Conclusion: Going green is an easy process that can save money, boost morale, and help educate patients while reducing the carbon footprint of any size medical practice.